The offering plate going digital: Factors affecting the adoption of electronic church giving (e-giving) - Ramos, Rommel Garcia (Animo Repository, 2018)
The giving of offerings has been part and parcel of worship since it was first introduced in the New Testament Church, as recorded in 1 Corinthians 16:2: Upon the first day of the week let every one of you lay by him in store, as God hath prospered him, that there be no gatherings when I come. (Authorized Version, The Holy Bible, King James Version, 1611). While the fast-changing computer technology continues to broaden the influence and reach of the church, various applications (apps) dramatically changed how the faithful give their offerings to the church. The introduction of electronic giving (e-giving) has gained wide acceptance in major churches in the western world, but it has yet to make a significant mark in Philippine churches. Since financial stewardship is one of its most serious concerns in order to sustain and further expand the diverse ministries of the church, this study examines several factors affecting the adoption of electronic giving (e-giving) application in giving their offerings among Baptist churches in the Philippines, particularly those located in three of the biggest cities of the National Capital Region (NCR).